Azolla-Anabaena as a Biofertilizer for Rice Paddy Fields in the Po Valley, a Temperate Rice Area in Northern Italy - Stefano Bocchi; Antonino Malgioglio (International Journal of Agronomy)
Azolla is a floating pteridophyte, which contains as endosymbiont the nitrogen-fixing cyanobacterium Anabaena azollae (Nostocaceae family). Widely cultivated in the Asian regions, Azolla is either incorporated into the soil before rice transplanting or grown as a dual crop along with rice. To examine the feasibility of its use in flooded rice fields sited in the Temperate European Areas, we carried out a series of experiments in PVC tanks during 2000–2002 in Po Valley (northern Italy) conditions, to study the growth-development dynamics and the resistance/tolerance to low temperatures and to commonly used herbicides of several different Azolla strains. Three out of five strains tested survived the winter, with an increase in biomass from March to May producing approximately 30–40 kg ha−1 of nitrogen. One of these strains, named “Milan”, emerged as the most resistant to herbicide and the most productive. Of the herbicides tested, Propanil permitted the survival of growing Azolla.